If `x = sqrt(sqrt(5) + 1) / sqrt(sqrt(5) – 1)`, then the value of `5x^2 – 5x – 1` will be.
Buying the Article: - The merchant buys using a 125 gram weight instead of 100 grams. This means he gets 25% more of the article for the same price. So, the cost price per 100 grams is effectively \(\frac{100}{125} = 0.8\) times the original cost price. Selling the Article: - The merchant sells usinRead more
Buying the Article:
– The merchant buys using a 125 gram weight instead of 100 grams. This means he gets 25% more of the article for the same price. So, the cost price per 100 grams is effectively \(\frac{100}{125} = 0.8\) times the original cost price.
Selling the Article:
– The merchant sells using an 80 gram weight instead of 100 grams. This means he gives 20% less of the article for the same price. So, the selling price per 100 grams is effectively \(\frac{100}{80} = 1.25\) times the original selling price.
Marking Up and Discount:
– The merchant marks up the price by 20% and then offers a 20% discount. The overall effect is calculated as follows:
\[ \text{Overall Factor} = \frac{125}{100} \times \frac{100}{80} \times \frac{120}{100} \times \frac{80}{100} = \frac{3}{2} \]
– This means the selling price is \(\frac{3}{2}\) times the cost price.
Overall Profit Percentage:
– Since the selling price is \(\frac{3}{2}\) times the cost price, the profit is \(\frac{1}{2}\) times the cost price.
– Therefore, the profit percentage is:
\[ \text{Profit Percentage} = \frac{1}{2} \times 100 = 50\% \]
Conclusion
The overall profit percentage is 50%.
See less
Solution Given: \[ x = \frac{\sqrt{\sqrt{5} + 1}}{\sqrt{\sqrt{5} - 1}} \] We need to find the value of \(5x^2 - 5x - 1\). Step 1: Simplify \(x\) Multiply the numerator and denominator by \(\sqrt{\sqrt{5} + 1}\): \[ x = \sqrt{\frac{(\sqrt{5} + 1)(\sqrt{5} + 1)}{(\sqrt{5} - 1)(\sqrt{5} + 1)}} = \sqrt{Read more
Solution
Given:
\[ x = \frac{\sqrt{\sqrt{5} + 1}}{\sqrt{\sqrt{5} – 1}} \]
We need to find the value of \(5x^2 – 5x – 1\).
Step 1: Simplify \(x\)
Multiply the numerator and denominator by \(\sqrt{\sqrt{5} + 1}\):
\[ x = \sqrt{\frac{(\sqrt{5} + 1)(\sqrt{5} + 1)}{(\sqrt{5} – 1)(\sqrt{5} + 1)}} = \sqrt{\frac{(\sqrt{5} + 1)^2}{5 – 1}} = \frac{\sqrt{5} + 1}{2} \]
Step 2: Substitute \(x\) into \(5x^2 – 5x – 1\)
\[ 5x^2 – 5x – 1 = 5\left(\frac{\sqrt{5} + 1}{2}\right)^2 – 5\left(\frac{\sqrt{5} + 1}{2}\right) – 1 \]
Simplify the expression:
\[ = 5 \times \frac{(3 + \sqrt{5})}{2} – \frac{5\sqrt{5} – 5 – 2}{2} \]
\[ = \frac{15 + 5\sqrt{5} – 5\sqrt{5} – 7}{2} \]
\[ = \frac{8}{2} \]
\[ = 4 \]
Conclusion
The value of \(5x^2 – 5x – 1\) is 4.
See less